EMERGENCE OF THE RESOURCE-BASED VIEW (RBV) AND ITS IMPACT ON FAMILY BUSINESS RESEARCH : LITERATURE REVIEW - Baros-Tóth, Ágnes (Tudásmenedzsment, 2024)
The emergence of the resource-based view (RBV) has changed the understanding of how companies grow and shifted the focus of examination from the firms external factors to the internal ones, more specifically to the companys resources so that the divergent developmental route of companies could be explained. The fundamental as sumption of RBV is that companies have different resources. If these resources are valuable, rare, inimitable, and non-substitutable (VRIN), they represent a lasting competitive advantage for the company. This study aims to discuss the literature review results to encapsulate the evolution of the resource-based view, its impact on family business research and theories, and its novel contributions to this field. RBV has been incorporated in family business research with the premise that family firms are thought to have resources that differ from those of their non-family counterparts because the family itself is considered a VRIN resource, through which the company can gain a competitive advantage and achieve higher organizational performance. A family business stood the test of time as it is still used even in recent research as a reference point. Familiness has also contributed to the emergence of other concepts such as the socioemotional wealth.